Carcinoid tumour of stomach and primary hyperparathyroidism: a new association. Issue 5 (May 1987) - Rode, J; Dhillon, A P; Cotton, P B; Woolf, A; O'Riordan, J L
Abstract : Three cases of carcinoid tumour of the stomach associated with primary hyperparathyroidism had the clinical and pathological features of a pluriglandular syndrome. Two of the patients showed multiple small polypoid carcinoids in the non-antral stomach, in conjunction with a parathyroid adenoma in one and parathyroid hyperplasia in the other case. One of these patients was also suffering from pernicious anaemia. A third patient had a large metastasising carcinoid arising in the gastric body and a parathyroid adenoma. Immunohistochemical stains for PGP 9.5 were positive in the carcinoids of all three cases. In all cases the carcinoids showed immunoreactivity for gastrin. A positive family history of endocrine hyperplasia and neoplasia was established in one case. It is suggested that patients with gastrointestinal carcinoids and their families should be evaluated for hyperparathyroidism, and patients with hyperparathyroidism presenting with upper gastrointestinal symptoms should undergo endoscopy to rule out gastric carcinoid tumours.